FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAKSANAAN EVALUASI PROGRAM BIMBINGAN DAN KONSELING - Aip Badrujaman (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The study aimed at revealing the factors affecting the implementation of the evaluation of guidance and counselling program in Junior Secondary Schools in East Jakarta. Employing descriptive method, the study was performed in March through September 2012. Using convenience sampling, the study identified 18 schools as samples. The study discovered two main factors causing guidance and counselling teachers not performing the guidance and counselling program: (a) inability to perform the evaluation and (b) the high load of the teachers’ tasks. The low factors include the result of guidance and counselling is difficult to measure, (b) incomplete data of guidance and counselling, (c) insufficient budget, (d) inability to set up relevant evaluation criteria, (e) unwillingness to reveal the existence of teacher-counsello, (f) the lack of gudance and counselling teachers, and (g) insufficient support from the svhool principa. The study suggests (a) to review the work load of the guidance and councelling teachers, (b) to develop the cooperation among related intitutions to imptove the competence of gudance and councelling teachers in the evaluation of guidance and counselling program.